1996
DOI: 10.1128/mcb.16.11.6229
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphotyrosine Interaction Domains of X11 and FE65 Bind to Distinct Sites on the YENPTY Motif of Amyloid Precursor Protein

Abstract: The phosphotyrosine interaction (PI) domains (also known as the PTB, or phosphotyrosine binding, domains) of Shc and IRS-1 are recently described domains that bind peptides phosphorylated on tyrosine residues. The PI/PTB domains differ from Src homology 2 (SH2) domains in that their binding specificity is determined by residues that lie amino terminal and not carboxy terminal to the phosphotyrosine. Recently, it has been appreciated that other cytoplasmic proteins also contain PI domains. We now show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
491
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(510 citation statements)
references
References 57 publications
(99 reference statements)
16
491
1
Order By: Relevance
“…In the Shc and IRS-1 PTB domains di erent residues recognize the bound pTyr, suggesting that these individual PTB domains might have independently acquired an ability to recognize phosphorylated Tyr (Eck et al, 1996;Zhou et al, 1995). Consistent with this view, PTB domains from proteins such as X11, Fe65 and Numb can bind tightly to non-phosphorylated peptides (Borg et al, 1996;Fiore et al, 1995;Li et al, 1997), suggesting that PTB domains may have originally developed as modules that recognize peptides with bturn structures, independently of phosphorylation. The diversity of peptide ligands recognized by PTB domains, and the signi®cant biological functions attributed to PTB-containing proteins, makes it important to understand the speci®city of ligand recognition in vivo.…”
Section: Introductionmentioning
confidence: 77%
“…In the Shc and IRS-1 PTB domains di erent residues recognize the bound pTyr, suggesting that these individual PTB domains might have independently acquired an ability to recognize phosphorylated Tyr (Eck et al, 1996;Zhou et al, 1995). Consistent with this view, PTB domains from proteins such as X11, Fe65 and Numb can bind tightly to non-phosphorylated peptides (Borg et al, 1996;Fiore et al, 1995;Li et al, 1997), suggesting that PTB domains may have originally developed as modules that recognize peptides with bturn structures, independently of phosphorylation. The diversity of peptide ligands recognized by PTB domains, and the signi®cant biological functions attributed to PTB-containing proteins, makes it important to understand the speci®city of ligand recognition in vivo.…”
Section: Introductionmentioning
confidence: 77%
“…FRS2 contains a putative PTB domain that is also related to the PTB domain of IRS-1 and, although it is not clear whether the interaction between the FGF receptor and FRS2 is direct, the FGF receptor does not contain an NPXY motif. Additionally, the PTB domain of Shc has been shown to interact with PTP-PEST through an NPLH motif (Charest et al, 1996) and the PTB domains of X11 and FE65 (Borg et al, 1996) have been shown to interact with non-phosphorylated NPXY motifs. Similarly, the PTB domain of Numb has been shown to interact with non-phosphorylated (Dho et al, 1998) and non-NPXY motif-containing Chien et al, 1998) targets.…”
Section: Discussionmentioning
confidence: 99%
“…Such sorting motifs function by binding specific adaptors to facilitate their selective import into budding carriers and ensure specificity in cargo selection and coat recruitment. The highly conserved phosphotyrosine binding (PTB) domains in all three Mint proteins have been shown previously to bind directly to the YENPXY motif of APP (Borg et al, 1996(Borg et al, , 1998Zhang et al, 1997;Sastre et al, 1998;Tanahashi and Tabira, 1999;Tomita et al, 1999;Ho et al, 2002;Araki et al, 2003). Other PTB domain containing proteins have similarly been shown to bind APP, including the Fe65 (Sabo et al, 1999) family, Dab2 (Howell et al, 1999), JIP1b (King et al, 2004), and ARH (Noviello et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…APP binds Mints via the YENPXY motif in its cytosolic tail (Borg et al, 1996;McLoughlin and Miller, 1996;Zhang et al, 1997;Okamoto and Sudhof, 1998) and in the absence of this motif cannot bind Mints (Tomita et al, 1999;Taru and Suzuki, 2004). We compared the post-Golgi traffic of wild-type APP 695 to that of APP 695 ⌬681-690 in HeLa cells, using the temperature block and release protocol for accumulating cargo at the TGN and following its exit, respectively.…”
Section: Knockdown Of Mint3 Alters App Trafficmentioning
confidence: 99%